2012
DOI: 10.1093/hmg/dds210
|View full text |Cite
|
Sign up to set email alerts
|

A persistent level of Cisd2 extends healthy lifespan and delays aging in mice

Abstract: The CISD2 gene, which is an evolutionarily conserved novel gene, encodes a transmembrane protein primarily associated with the mitochondrial outer membrane. Significantly, the CISD2 gene is located within the candidate region on chromosome 4q where a genetic component for human longevity has been mapped. Previously, we have shown that Cisd2 deficiency shortens lifespan resulting in premature aging in mice. Additionally, an age-dependent decrease in Cisd2 expression has been detected during normal aging. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 44 publications
(59 reference statements)
2
77
0
Order By: Relevance
“…Previously, we have shown that there is an age‐dependent decrease in Cisd2 expression levels within the brain and the femoris muscle using C57BL/6 WT mice (Chen et al., 2010; Wu et al., 2012). The mean lifespan of C57BL/6 mice is 25.5 ± 3.9 months ( n  = 50) in our mouse facility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that there is an age‐dependent decrease in Cisd2 expression levels within the brain and the femoris muscle using C57BL/6 WT mice (Chen et al., 2010; Wu et al., 2012). The mean lifespan of C57BL/6 mice is 25.5 ± 3.9 months ( n  = 50) in our mouse facility.…”
Section: Resultsmentioning
confidence: 99%
“…The mean lifespan of C57BL/6 mice is 25.5 ± 3.9 months ( n  = 50) in our mouse facility. In the femoris muscle, there was an average 38% and 57% decrease in the Cisd2 protein level during middle age (12‐month‐old [12M]) and during old age (24M), respectively, compared with young (3M) mice (Wu et al., 2012). Strikingly, in the gastrocnemius, there was a much higher decline, namely a ~70% decrease in Cisd2 protein level during middle/old age (Figure 1a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of mitochondria in cancer cell function could be linked to the enhanced accumulation of iron and reactive oxygen species (ROS) in mitochondria of cancer cells, which is thought to result from the increased metabolic and energetic demands of the transformed phenotype (7). An interesting, recently discovered group of proteins that could link iron and ROS homeostasis with mitochondrial function in cancer cells are NEET proteins (8-15).NEET proteins [mitoNEET (mNT; CISD1), Nutrient-deprivation autophagy factor-1 (NAF-1; CISD2), and CISD3] are a class of iron-sulfur proteins involved in several human pathologies, including diabetes, cystic fibrosis, Wolfram syndrome 2, neurodegeneration, and muscle atrophy (16)(17)(18)(19)(20)(21)(22). mNT and NAF-1 are localized to the outer mitochondrial membrane.…”
mentioning
confidence: 99%
“…NEET proteins [mitoNEET (mNT; CISD1), Nutrient-deprivation autophagy factor-1 (NAF-1; CISD2), and CISD3] are a class of iron-sulfur proteins involved in several human pathologies, including diabetes, cystic fibrosis, Wolfram syndrome 2, neurodegeneration, and muscle atrophy (16)(17)(18)(19)(20)(21)(22). mNT and NAF-1 are localized to the outer mitochondrial membrane.…”
mentioning
confidence: 99%